Improving the prognosis of renal patients: The effects of blood flow‐restricted resistance training on redox balance and cardiac autonomic function. Issue 4 (3rd March 2021) - de Deus, Lysleine Alves; Neves, Rodrigo Vanerson Passos; Corrêa, Hugo de Luca; Reis, Andrea Lucena; Honorato, Fernando Sousa; Silva, Victor Lopes; de Araújo, Thaís Branquinho; Souza, Michel Kendy; Sousa, Caio Victor; Simões, Herbert Gustavo; Prestes, Jonato; Silva Neto, Luiz Sinésio; et al.
Abstract : New Findings: What is the central question of this study? Can resistance training with and without blood flow restriction improve redox balance and positively impact the autonomic cardiac modulation in chronic kidney disease patients? What is the main finding and its importance? Resistance training with and without blood flow restriction improved antioxidant defence (paraoxonase 1), decreased the pro‐oxidative myeloperoxidase, improved cardiac autonomic function and slowed the decrease in renal function. We draw attention to the important clinical implications for the management of redox balance and autonomic cardiac function in chronic kidney disease patients. Abstract: Patients with chronic kidney disease (CKD) are prone to cardiovascular diseases secondary to abnormalities in both autonomic cardiac function and redox balance [myeloperoxidase (MPO) to paraoxonase 1 (PON1) ratio]. Although aerobic training improves both autonomic balance and redox balance in patients with CKD, the cardioprotective effects of resistance training (RT), with and without blood flow restriction (BFR), remain unknown. We aimed to compare the effects of RT and RT+BFR on antioxidant defence (PON1), pro‐oxidative status (MPO), cardiac autonomic function (quantified by heart rate variability analysis) and renal function. Conservative CKD (stages 1 to 5 who do not need hemodialysis) patients ( n  = 105, 33 female) of both sexes were randomized into three groups: control (CTL; 57.6 ± 5.2 years; body mass index, 33.23 ± 1.62 kg/m 2 ), RT (58.09 ± 6.26 years; body mass index 33.63 ± 2.05 kg/m 2 ) and RT+BFR (58.06 ± 6.47 years; body mass index, 33.32 ± 1.87 kg/m 2 ). Patients completed 6 months of RT or RT+BFR on three non‐consecutive days per week under the supervision of strength and conditioning professionals. Training loads were adjusted every 2 months. Heart rate variability was recorded with a Polar‐RS800 and data were analysed for time and frequency domains using Kubios software. The redox balance markers were PON1 and MPO, which were analysed in plasma samples. Renal function was estimated as estimated glomerular filtration rate. The RT and RT+BFR decreased pro‐oxidative MPO (RT, ∼34 ng/ml and RT+BFR, ∼27 ng/ml), improved both antioxidant defence (PON1: RT, ∼23 U/L and RT+BFR, ∼31 U/L) and cardiac autonomic function (R–R interval: RT, ∼120.4 ms and RT+BFR, ∼117.7 ms), and slowed the deterioration of renal function ( P  < 0.0001). Redox balance markers were inversely correlated with heart rate variability time‐domain indices. Our data indicated that both training models were effective as non‐pharmacological tools to increase the antioxidant defences, decrease oxidative stress and improve the cardiac autonomic function of CKD patients. Abstract :